(untitled) (Bangladesh Journal of Medical Biochemistry, 2019)
Obesity has become a global epidemic and has been found to be associated with numerous comorbidities. Body mass index (BMI) based classification of obesity is simple but co-morbidities do not affect all obese and overweight people. The present study was aimed to find out the frequency of metabolic phenotypes in different BMI groups using metabolic syndrome (MetS) criteria and cardiometabolic disabilities (CA) criteria and also to find out an appropriate method for defining metabolic health among adult population attending out patient department of Bangabandhu Sheikh Mujib Medical University (BSMMU). This cross-sectional analytical study was carried out in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU) from March 2016 to February 2017. By non probability sampling, a total of 1023 study subjects were selected from apparently healthy adult individuals attending outpatient department of BSMMU. The study subjects were grouped into three body mass index classes and also further categorized into six groups according to metabolically unhealthy or healthy phenotypes by presence or absence of metabolic syndrome (MetS) criteria as well as cardiometabolic disabilities (CA) criteria respectively. Then agreement among different metabolic phenotypes based on these two criteria were observed. Frequency of different metabolic phenotypes i,e metabolically healthy normal weight (MHNW), metabolically obese normal weight (MONW), metabolically healthy over weight (MHOW), metabolically obese over weight (MOOW), metabolically healthy obese (MHO) and metabolically unhealthy obese (MUO) were 12.3%, 6.9%, 21.4%, 27.7%, 7.7%, 23.9% by MetS criteria and 7.7%, 11.5%, 11.6%, 37.4%, 6.1%, 25.6% by CA criteria respectively. MOOW followed by MUO were found to be predominant among all phenotypes. Fare agreement was found between two criteria in case of normal weight and overweight groups and good agreement was found in case of obese groups. From this study, it may be concluded that, attention should be given to the metabolically obese phenotypes in different BMI classes to reduce co-morbidities. Bangladesh J Med Biochem 2018; 11(1): 1-8